Antibacterial Activity of Ethanol Extract of Arabian Lotus Leaves (Ziziphus spina-christi L.) and Bioautography TLC Analysis of Several Pathogenic Bacteria - Herlina Rante; Marni Pabisa; Burhanuddin Taebe (Fakultas MIPA UNM, 2023)
Bidara arab leaves (Ziziphus spina-christi L), contain various potentially health-beneficial compounds, including antibacterial agents. The aim of this study was to determine the antibacterial activity of ethanolic leaf extract of Ziziphus spina-christi L. in inhibiting the growth of pathogenic bacteria. The leaves of Bidara arab were macerated using 70% ethanol, followed by the agar diffusion method to evaluate the antibacterial activity. Subsequently, bioautography analysis using TLC and phytochemical screening of the active extract were conducted. The results of the antibacterial activity test using the ethanolic leaf extract of Ziziphus spina-christi L. showed antibacterial activity at a concentration of 2 mg/paper disk, with inhibition zone diameters of 19.44 mm for Bacillus subtillis, 17.06 mm for Escherichia coli, 16.32 mm for Staphylococcus aureus, 12.96 mm for Pseudomonas aeruginosa, and 14.50 mm for Salmonella typhi. The TLC-bioautography analysis of the ethanolic leaf extract of Ziziphus spina-christi L. against Bacillus subtillis exhibited inhibition at Rf 0.96, Escherichia coli at Rf 0.31, Staphylococcus aureus at Rf 0.89, while Salmonella typhi did not show inhibitory activity. Phytochemical screening results indicated that the ethanolic leaf extract of Bidara arab is suspected to contain flavonoids, terpenoids, and tannins.